Efeitos da variação de parâmetros na vibração mecânica em condições simuladas de transporte de frangos de corte - Macêdo, Luiza Diniz (2024)
During transportation, broiler chickens are subjected to high levels of stress, one of those stress sources is due the mechanical vibrations, it’s intensity can vary due the road conditions, lorry’s conditions, travel’s length, broiler chicken’s density inside the crate, and environmental conditions. The research field that encompasses mechanical vibration analysis during chicken transportation is still sparse, which makes challenging to know the true impacts of this variable on animals. This research analyzed parameters that influence the mechanical vibration from broiler chicken transportation, this analysis was conducted due to the high levels of stress that occurs during the pre-slaughter phase, which can result in problems like quality loss or even dead-on-arrival cases. Laboratory, computational, and field analysis were conducted, in order to analyze the influence of parameters and environmental conditions (temperature and airflow), on mechanical vibration. A physical and computational model was stipulated, thus avoiding subjecting animals to tests, in order to emulate the environmental conditions in which the broiler chickens are subjected during transportation. Furthermore, the goal was to identify the variables that could be changed or improved during pre-slaughter activities, in order to grant better welfare for the animal’s during transportation. The field analysis utilized sensors attached to crates on the first and last position on a 9-crate stack, in diagonal spots. Therefore, it was possible to access that the weight on top of the analyzed crate, position relative to the stack, and localization of the broiler chicken on the crate influence both the frequency and RMS value obtained. Concerning the impact that the crates received, measured on the free-fall and drag-and-drop tests, a value of 533.66 J were obtained, due the potential energy that resulted from the fall. During the field tests, it was possible to verify that the values of RMS surpassed the established values regarding human safety, observed values were 9.64, 0.67, and 4.29 m/s2 respectively on X, Y, and Z axis. The results obtained for incident frequency, during the laboratory tests, showed that the crates most affected were on both extremes of the stack (base crate and top crate). By comparing the obtained data with the vibrational comfort levels for humans, it is inferred that the animals subjected to these conditions are in a state of discomfort.